2014
DOI: 10.1177/1359105314547941
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the lives of women with polycystic ovary syndrome: A photovoice investigation

Abstract: Polycystic ovary syndrome affects 6  percent of women. Symptoms include hirsutism, acne, and infertility. This research explores the impact of polycystic ovary syndrome on women's lives using photovoice. Nine participants photographed objects related to their quality of life and made diary entries explaining each photograph. Three themes emerged from thematic analysis of the diaries: control (of symptoms and polycystic ovary syndrome controlling their lives), perception (of self, others, and their situation), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…This study found that digital magazines depicted PCOS as a barrier to having children that hindered women’s roles as wives and mothers. These findings are consistent with Williams and colleagues’ findings that women perceive PCOS as interrupting their plans to start a family and the timing of starting a family [ 23 , 77 ]. The portrayal of PCOS as a possible barrier to breastfeeding in women’s magazines supports nascent research that suggests that women living with PCOS experience breastfeeding challenges.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study found that digital magazines depicted PCOS as a barrier to having children that hindered women’s roles as wives and mothers. These findings are consistent with Williams and colleagues’ findings that women perceive PCOS as interrupting their plans to start a family and the timing of starting a family [ 23 , 77 ]. The portrayal of PCOS as a possible barrier to breastfeeding in women’s magazines supports nascent research that suggests that women living with PCOS experience breastfeeding challenges.…”
Section: Discussionsupporting
confidence: 91%
“…Personal responsibility is certainly important in managing one’s health. Indeed, women with PCOS report that diet and exercise are critical in controlling their weight and other PCOS symptoms [ 77 ]. However, it is important to keep in mind that personal responsibility discourse that blames individuals for poor lifestyle choices and poor health can perpetuate stigma and discrimination toward obese individuals and hinder efforts that address environmental and structural barriers to health [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scale items were developed from qualitative research exploring QoL in women with PCOS (see Williams, Sheffield and Knibb, 2014 ; 2015 ) and a comprehensive review of the literature. Items were reviewed by an expert panel (n = 5) of PCOS healthcare professionals and psychologists specialising in disease-specific scale development ( DeVellis, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent qualitative literature also supports the notion that the PCOSQ does not reflect QoL, as defined by the World Health Organisation (WHO) (WHOQOL Group, 1994) and women with the condition ( Snyder, 2006 ; Williams et al, 2014 , 2015 ). The WHOQOL Group (1994) proposes that there are six domains of QoL: physical health, psychological health, level of independence, social relationships, and environment and spirituality/religion/personal beliefs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation